Elements Testings Distortion of the Abuse of Authority Based on the Government Administration Law and Corruption Crime - Putri Nurmala Sari Siahaan (Corruptio, 2021)
It is expected that the existence of the Government Administration Law is expected to be a solution so that there is no expression of “bad suspicion” against government officials in making decisions accused of causing losses to state finances. In addition, the GA Law is expected to become a reference for government officials in making decisions so that there is no abuse of authority. These two cargoes are a small part that is regulated in the GA Law. Regarding the abuse of authority itself, there have been specific regulations derived from the Supreme Court Regulation Number 4 of 2015 concerning Guidelines for Procedures in the Assessment of the Elements of Abuse of Authority. The problem that arises in examining the elements of abuse of power lies in the law enforcement process. The Perma Abuse of Authority states that the Court has the authority to accept, examine, and decide upon the appraisal request whether there is an abuse of authority in the Decisions and/or Actions of Government Officials before the criminal process. From the field facts, through case analysis, there are findings that government officials who submitted applications for the element of abuse of power did not heed the provisions in the Perma. In the two cases discussed, it appears that, in fact, the instrument of testing whether or not there is an element of abuse of authority is only used as an attempt to hide oneself from being ensnared from corruption. It is as if the petitioner has become a victim in the act of abuse of authority over the action or decision he has taken. However, the facts show otherwise where the applicant legally and convincingly committed a criminal act of corruption. It can be said that the use of the concept of testing the elements of abuse of authority is intended to be deviant and biased from the ideals of the concept.